The economic geographies of organized crime - Hall, Tim (Guilford Press, 2018)
Geography and organized crime -- Contemporary organized crime -- Measuring and researching organized crime -- The organization of criminal enterprises -- The spatialities of organized crime -- Criminal mobilities -- Responding to organized crime -- Toward economic geographies of organized crime